ASSURING WORSHIP ACCURACY: ENGAGING CLASSICAL ISLAMIC JURISPURDENCE AND MODERN FALAK SUDIES - Pepep Puad Muslim (KANUN:JURNAL ILMU HUKUM, 2025)
The study analyses classical and contemporary literature to identify areas of convergence and tension between hisab (astronomical calculation) and rukyat (empirical observation) as two complementary methodologies in Islamic astronomy (‘ilm al-falak), and examines how Islamic jurisprudence (fiqh) can harmonize both approaches to ensure the accuracy and unity of Muslim worship practices. The central issue addressed is the epistemological gap between traditional fiqh, which normatively emphasizes rukyat as the textual command of the Prophet, and modern astronomy, which prioritizes the precision of hisab through scientific computation. This integration is urgently needed to preserve the kesatuan ummah (unity of the Muslim community) and to enhance the legitimacy and consistency of worship times, Qibla direction, and Hijri calendar determination. Methodologically, this research employs a qualitative–normative design with an interdisciplinary framework that combines fiqh principles, particularly the legal maxim taghayyuru al-ahkam bi taghayyuri al-azman wal-amkinah (laws may change due to time and place), with the empirical logic of modern astronomy. The findings reveal that integrating hisab and rukyat under a jurisprudential framework not only maintains the normative integrity of Islamic law but also reinforces scientific accuracy and social cohesion in religious observances. This paper proposes an operational model of fiqh al-falak al-mu‘āṣir (contemporary astronomical jurisprudence) that bridges tradition and modernity, ensuring that Islamic astronomical practices remain both legally valid and scientifically precise.